Ethnomedicinal plants used by local inhabitants of Jakholi block, Rudraprayag district, western Himalaya, India - Ankit Singh; Mohan C. Nautiyal; Ripu M. Kunwar; Rainer W. Bussmann (BMC, 2017)
Abstract Background Ethnomedicinal knowledge of the Indian Himalayas is very interesting because of the wide range of medicinal plants used in traditional medical practice. However, there is a danger of knowledge being lost because the knowledge sharing is very limited and passed on orally. The present study is the first ethnomedicinal study in Jakholi area of Rudraprayag district of Northwestern India. The aim of present study was to identify traditional medicinal plants used by the inhabitants to treat different ailments and document the associated knowledge of these medicinal plants. Methods An ethnomedicinal survey was carried out in 72 of 133 villages and alpine pastures of Jakholi block (800-4000 m asl). Door to door surveys and group discussions, applying semi-structured questionnaires were conducted with traditional healers and villagers in local language (Garhwali). Informant Consensus Factor (ICF) was computed to analyse collected ethnomedicinal data. Results A total of 78 species (Gymnosperms 3 species, Monocotyledons 12 and 63 Dicotyledons) belonging to 73 genera in 46 families were identified to treat 14 different ailments categories. Most dominant family is Asteraceae (5 species). In disease treated categories, Diseases of the skin (DE) have the highest proportion (29.55%) followed by Gastro- intestinal disorder (GA) (25.89%). The most life form of plants used was herb (56%) followed by tree (23%) while root was the most frequently used part of the plants and the traditional preparation was mainly applied in the form of paste (37%). The highest ICF value (0.99) was found for hair ailments (HA) followed ophthalmologic complaints (OP) and mental afflictions (MA) (0.98). Conclusions The present study provides valuable information about traditional knowledge of medicinal plants of Jakholi Block in the Northwestern Himalaya, India. Local communities still possess large traditional knowledge of plants and their therapeutic uses and that the link of that traditional knowledge to modern research could be of importance for the isolation of new phytotherapeutic compounds leading to the development of novel therapeutic active agents. Some of the ethnomedicinal plants are facing high threats and are becoming rare, and conservation initiatives are needed to conserve them for sustainable management in the region.